Compensatory role of the NBCn1 sodium/bicarbonate cotransporter on Ca2+-induced mitochondrial swelling in hypertrophic hearts - Vargas, Lorena Alejandra (2017)
NBC Na+/HCO3 − cotransporter (NBCn1) and NHE1 Na+/H+ exchanger have been associated with cardiac disorders and recently located in coronary endothelial cells (CEC) and cardiomyocytes mitochondria, respectively. Mitochondrial NHE1 blockade delays permeability transition pore (MPTP) opening and reduces superoxide levels, two critical events exacerbated in cells of diseased hearts. Conversely, activation of NBCn1 prevented apoptosis in CEC subjected to ischemic stress. We characterized the role of the NHE1 and NBCn1 transporters in heart mitochondria from hypertrophic (SHR) and control (Wistar) rats. Expression of NHE1 was analyzed in left ventricular mitochondrial lysates (LVML), by immunoblots. NHE1 expression increased by ~40% in SHR compared to control (Pï¿½